Au/Ag nanostructures on PMMA surface - Brito, Paula; Souza, Thiago; Gomes, Rodrigo; Ferreira, Nilson; Macêdo, Marcelo (Scientia Plena, 2011)
<!–[if gte mso 9]> Normal 0 21 false false false PT-BR X-NONE X-NONE MicrosoftInternetExplorer4 <![endif]–><!–[if gte mso 9]> <![endif]–><!–[if gte mso 10]> <mce:style><! /* Style Definitions */ table.MsoNormalTable mso-style-name:"Tabela normal"; mso-tstyle-rowband-size:0; mso-tstyle-colband-size:0; mso-style-noshow:yes; mso-style-priority:99; mso-style-qformat:yes; mso-style-parent:""; mso-padding-alt:0cm 5.4pt 0cm 5.4pt; mso-para-margin:0cm; mso-para-margin-bottom:.0001pt; mso-pagination:widow-orphan; font-size:11.0pt; font-family:"Calibri","sans-serif"; mso-ascii-font-family:Calibri; mso-ascii-theme-font:minor-latin; mso-fareast-font-family:"Times New Roman"; mso-fareast-theme-font:minor-fareast; mso-hansi-font-family:Calibri; mso-hansi-theme-font:minor-latin; mso-bidi-font-family:"Times New Roman"; mso-bidi-theme-font:minor-bidi; –> <!–[endif]–>Densely and uniformly distributed nanoholes in poly(methyl methacrylate) (PMMA) films have been manufactured and analyzed, as was the behavior of metallic particles deposited onto the films. The films had been prepared by spin-coating and characterized by atomic force microscopy. The measured diameter and depth of the nanoholes formed on the films had presented values around 200 nm and 12 nm, respectively. An analysis of the organization of both silver and gold film-deposited nanoparticles showed a tendency to agglomerate on the nanohole edges on the polymeric film surface. We verified that the films are favorable for use as templates in a self-assembly processes.